The BCMA-Targeted Fourth-Generation CAR-T Cells Secreting IL-7 and CCL19 for Therapy of Refractory/Recurrent Multiple Myeloma - Duan, Deming; Wang, Keke; Wei, Cheng; Feng, Dudu; Liu, Yonghua; He, Qingyan; Xu, Xing; Wang, Chunling; Zhao, Shuping; Lv, Leili; Long, Jing; Lin, Danni; et al. (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) technology has revolutionized cancer treatment, particularly in malignant hematological tumors. Currently, the BCMA-targeted second-generation CAR-T cells have showed impressive efficacy in the treatment of refractory/relapsed multiple myeloma (R/R MM), but up to 50% relapse remains to be addressed urgently. Here we constructed the BCMA-targeted fourth-generation CAR-T cells expressing IL-7 and CCL19 (i.e., BCMA-7×19 CAR-T cells), and demonstrated that BCMA-7×19 CAR-T cells exhibited superior expansion, differentiation, migration and cytotoxicity. Furthermore, we have been carrying out the first-in-human clinical trial for therapy of R/R MM by use of BCMA-7×19 CAR-T cells (ClinicalTrials.gov Identifier: NCT03778346), which preliminarily showed promising safety and efficacy in first two enrolled patients. The two patients achieved a CR and VGPR with Grade 1 cytokine release syndrome only 1 month after one dose of CAR-T cell infusion, and the responses lasted more than 12-month. Taken together, BCMA-7×19 CAR-T cells were safe and effective against refractory/relapsed multiple myeloma and thus warranted further clinical study.